Entrepreneur – Creative Person - Shokhsanam Dilshodjonovna Dovlatova (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
The article reveals that an entrepreneur is a creative person. The characteristics of the entrepreneur were considered. Particular attention is paid to the creative approach to the production process.